Cloning and bioinformatics analysis of key gene ShOMT3 of podophyllotoxin biosynthesis pathway in Sinopodophyllum hexandrum. - Wei Liu; Haona Gao; Dan Zhao; Shuying Li; Lu Li; Xiufang Zhao; Zheng Zhang; Dongxue Yin (PLoS ONE)
Sinopodophyllum hexandrum (S. hexandrum) is an endangered traditional Chinese medicine as abundant podophyllotoxin with powerful anticancer activity. In this study, the rootstalks of S. hexandrum from different geographical locations in China [S1 (Gansu) and S2 (Shaanxi)] were used as research materials to clone the key gene pluviatolide O-methyltransferase 3 (ShOMT3) in the podophyllotoxin biosynthetic pathway. Subsequently, bioinformatics analysis of the ShOMT3 gene and its encoded protein was subjected to bioinformatics analysis using various analysis software including ProtParam, DeepTMHMM, SubLoc, Signal-P 5.0, and Swiss-model. The results of the analysis revealed that the CDS region of the ShOMT3 gene is 1119 bp long, encoding 372 amino acids. The theoretical molecular weight of the ShOMT3 protein is 41.32784 kD, and the theoretical isoelectric point (pI) is 5.27. The instability coefficient of the protein is 46.05, the aliphatic index is 93.58, and the grand average of hydropathicity (GRAVY) is 0.037, indicating that it is an unstable hydrophobic protein. The protein does not contain transmembrane domains or signal peptides, indicating that it is a non-secreted protein. Secondary structure prediction results suggests that the protein consists of alpha helices, random coils, extended strands, and beta-turns. Tertiary structure prediction results suggests that the protein functions as a monomer. In the phylogenetic tree, the ShOMT3 protein has the highest homology with Podophyllum peltatum (P. peltatum). The successful cloning and bioinformatics analysis of the ShOMT3 gene provide theoretical basis and excellent genetic resources for the molecular regulatory mechanism analysis of the podophyllotoxin biosynthetic pathway and molecular breeding in S. hexandrum.